Asas Legalitas dalam Hukum Pidana dan Asas-Asas dalam Hukum Pidana - Diah Dwi Rizki Putri Qomariyah; Vira Hidayatur Rahma; Muhammad Alaina Fadli; Fikry Fathurrahman; Muhammad Rafi Irwanzah (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This article examines the position and development of the principle of legality as a fundamental pillar of criminal law within the Indonesian legal system, and its relationship with other core principles of criminal law. Drawing on a qualitative method with a normative juridical and descriptive-analytical approach, the study analyzes statutory provisions in the current KUHP, the new Criminal Code enacted through Law Number 1 of 2023, as well as relevant doctrines and previous research, and compares them with the construction of legality in Islamic criminal law. The analysis shows that the new Criminal Code essentially maintains the classical formulation of legality and the non‑retroactivity principle, while at the same time introducing important innovations, including limited recognition of living law and adjustments to respond to contemporary forms of crime. These developments are discussed not only at the dogmatic level, but also in light of sociological perspectives on criminal law. The findings indicate that the principle of legality and the accompanying principles of criminal law (territorial, personal, universal, locus delicti, tempus delicti, and others) function as key instruments of social control that define the reach of state power in regulating and sanctioning deviant behavior. Proper and consistent implementation of legality strengthens legal certainty, protects individuals from arbitrary punishment, and enhances public trust in law enforcement institutions; conversely, inconsistency and overly broad discretion tend to erode perceptions of justice and legitimacy. By integrating normative legal analysis with sociological insights among others inspired by Durkheim’s view of law as an expression of social solidarity and Weber’s notion of formal rationalization the article argues that the reform of Indonesia’s criminal law should aim at a balanced configuration between legal certainty, substantive justice, and social responsiveness in a pluralistic society.